INTERNALIZATION OF STUDENT CHARACTER EDUCATION THROUGH EXTRACURRICULAR PROGRAMS AT ASSALAM JUNIOR HIGH ISLAMIC BOARDING SCHOOL MASARAN - Dyah Ayu Chusnul Chotimah; Nurul Latifatul Inayati; Ari Anshori (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2019)
Assalam Junior High Islamic Boarding School Masaran is the first Integrated Islamic-based school in the Masaran area. Standing in a rural area where the majority of the population is unfamiliar with private Islamic schools, this school has the aim of producing graduates who have moral values, have independent personalities and are able to master science and technology. In producing the graduates who have moral values the school has added character education. The need for character education to instill values that include components of knowledge, awareness and actions to carry out these values is applied through extracurricular activities. The purpose of this research is to describe the process of internaliztionstudent character education through extracurricular programs at Assalam Junior High Islamic Boarding School Masaran along with its supporting and inhibiting factors.This type of research is field research with qualitative descriptive approaches. Data collection techniques using observation methods, interviews and documentation analyzed through the process of collecting data, reducing data, presenting data and drawing conclusions using the deductive method and using the validity of the data with triangulation of sources. The results of this study explained that in the process of internaliztionstudent character education through extracurricular programs at Assalam Junior High Islamic Boarding School Masaran by three compulsory extracurricular programs namely Qira'ah, Taekwondo and Scout. (1) Qira’ah, the method used is the provision of theory which is then put into practice. The expected character is that students behave well while giving rise to the morals of the Qur'an;(2) Taekwondo, the method used is an exemplary method at the end of the learning session. The expected character is responsibility, courage and respect for others;(3) Scouting, the method used is reward-punishment, giving examples and training. The desired character is a character that is bertauhid, moral mercy and love of nature.The supporting factors of this program are the availability of facilities and infrastructure and support from the school. While the lack of interest in students is evidenced by the lack of responsibility when joining the extracurricular program is the inhibitory factor.